Mycelial growth inhibition of basidiomyceteous fungi by extracts of anacardium occidentale linn, bridelia ferruginea benth and ficus sur forsskal (2010)
Aqueous extracts of the leaves, barks and the roots of Anacardium accidentale, Bridelia ferruginea and Ficus sur were bioassayed at full concentrations for their antifungal potentials by determining their inhibitory effects on the mycelia growth of Rigidiporus lignosus and Coriolopsis occidentalis. Statistically significant differences at p<0.05 between plants and plant parts were studied as well as the resistance of the test fungi to treatment with different plant part extracts. The results indicated that all the plants and their parts contain water soluble active ingredients with antifungal properties which proved to be good inhibitors of the growth of R. lignosus and C. occidentalis. The crude extracts from all the parts of Fictus sur performed best of all extracts as it totally inhibited the mycelia growth of R. lignosus and C. occidentalis